Cultural Da’wah and Political Communication in Colonial Java: A Study of Traditional Islamic Discourse and Social Resistance - Addiansyah, M. Nur Rofiq; Khofifah, Melina Nurul; Susanti, Endang; Wahyuningsih, Sri (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2026)
This study explores the cultural and traditional Islamic political da’wah represented by KH. Asnawi, a conventional scholar who integrated da’wah, education, and socio-political activism within the context of Dutch colonialism. The research addresses the need to reinterpret da’wah not only as a religious activity but as a form of political communication that nurtures social awareness and cultural resistance. The study focuses on how KH. Asnawi integrated da’wah, education, and organizational activism to strengthen Islamic identity and mobilize collective resistance. Using a qualitative method that combines historical and documentary approaches, the analysis draws on texts such as Fasholatan, archival sources, and organizational records. The findings show that KH. Asnawi employed cultural and persuasive communication strategies through poetry, madrasah education, and Islamic organizations (Sarekat Islam and Nahdlatul Ulama). His da’wah functioned at cognitive, affective, and behavioral levels, transforming individual piety into social solidarity. Viewed through Social Penetration Theory and Persuasive Communication Theory, his strategy demonstrates how religious communication can evolve from emotional engagement to political mobilization. The study contributes to the scholarship of Islamic communication by revealing da’wah as a contextual and transformative process that bridges spirituality, culture, and social change.